The use of attractants in the application of food-baits against termites - Ganieva, Zumrat; Khashimova, Mukhabbat; Rustamov, Kakhraman; Akhmedov, Voxid (Acta Biologica Sibirica, 2023)
The article presents the results of scientific research on the identification of attractants in the development of food-baits against termites of the genus Anacanthotermes.